Project management for engineering, business and technology - Nicholas, John M.; Steyn, Herman (Abingdon, Ox : Routledge, 2017)
This title addresses project management across all industries. First covering the essential background, from origins and philosophy to methodology, it is dedicated to concepts and techniques for practical application. Coverage includes project initiation and proposals, scope and task definition, scheduling, budgeting, risk analysis, control, project selection and portfolio management, programme management, project organization, and all-important 'people' aspects-project leadership, team building, conflict resolution and stress management.
Part 1. Philosophy and concepts -- Part 2. Project Life Cycle -- Part 3. Systems and procedures for planning and control -- Part 4. Organization Behavior -- Part 5. Project Management in the corporate context.
Includes index.
Keywords: BUSINESS MANAGEMENT